Efficacy of a Low-Cost Weight-Bearing Sensitivity Incentivator After Lower Limb Surgery: A Pilot Randomised Controlled Trial - Alessandro Manelli; Isella Carola; Fabrizio Mancini; Schiavone Nicola; Rathlef Daniel; Marina Protasoni; Andrea Brambilla; Piero Antonio Zecca (Applied Sciences)
Background: Accurate partial weight-bearing (PWB) is essential for postoperative recovery after lower limb surgery, yet patients often fail to maintain load within clinically meaningful thresholds. Methods: In this pilot randomised controlled trial with 1:1 concealed allocation, 34 inpatients aged 18–85 who underwent femoral fracture fixation, hip arthroplasty, or knee arthroplasty were enrolled and followed for 14 days. Participants were randomly assigned to either standard physiotherapy or the same protocol with a low-cost tactile insole (“incentiviser”) that provides mechanical feedback when the prescribed 20% body weight (BW) load is exceeded. The primary outcome was absolute deviation from target load, with a minimal clinically important difference (MCID) of ±2 kg. Results: In total, 88% of the intervention group achieved the MCID at discharge versus 24% of controls. The between-group difference in final load error was 10.8 kg (95% CI: −15.2 to −6.4), with a large effect size (Cohen’s d = 1.71). No significant differences were found in pain (NRS) or walking distance (6MWT) between groups. Conclusions: The tactile incentiviser significantly improved PWB accuracy within 14 days, meeting MCID thresholds in most cases. Its low cost and simplicity make it promising for routine or home-based use. Limitations include the small sample, diagnosis heterogeneity, and absence of a sham control. Larger multicentre trials are needed to confirm generalisability and long-term clinical impact.